"Hooking Up" and Hanging Out: Casual Sexual Behavior Among Adolescents and Young Adults Today - Christy Daniel; Kate Fogarty (EDIS)
FCS2279, a 3-page fact sheet by Christy Daniel and Kate Fogarty, addresses the concerning trend of casual sexual "hook-ups" among teens today. It explains what behaviors and attitudes predispose teens to "hooking up" and gives suggestions to parents who are hoping to prevent this behavior. Published by the UF Department of Family, Youth and Community Sciences, October 2007.